Fārābi's "Utopia" and its relevance to the Greek Theory of Emanation (As an Islamic civilization perspective) - Mohd. Shamsuddin, Salahuddin; Asmad , Arman b.; Hj. Ahmad, Siti Sara Binti (Advances in Social Sciences Research Journal, 2019)
"Utopia" is the expression that recalls the dreams of wise men and philosophers from Plato to Thomas Moore to the modern age, as each has his own view about that hopeful virtuous life. Fārābi, nicknamed “The Second Teacher” was the first developed an integrated concept of the "utopia" as an Arab-Islamic perspective. This book includes thirty-seven chapters, in which Fārābi dealt with five main topics, namely: The divine Self is represented as the first existent. The world with its assets; inanimate objects, living beings, celestial bodies, human soul, ethics and its basic principles, and finally the human need to the society. Fārābi formulates a perfect image of the cooperation among the members of the society where the justice prevails and its inhabitants are happy, opposite to the ignorant cities. He mentions some of the qualities of the first president, the founder of utopia succeeds by the second presidents, including: He must be a wise and philosopher, along with the other qualities in the knowledge of laws and Sunnah, must have the ability to diligence and devise the judgments and be prepared with his body and apparatus to protect the country and conduct the war. We can say that this president is "Plato in the dress of the Prophet Muhammad. This book: "Views of the people of the utopia" played a fundamental role in the history of Islamic thought, although he apposed in the first part of his book, especially on the subject: Neoplatonism and distinction between the wisdom and Sharia.